Role of Innovation in Testing Environment Kuznets Curve: A Case of Indonesian Economy - Yusuf, Muhammad; Sabara, Zakir; Wekke, Ismail Suardi (International Journal of Energy Economics and Policy, 2018)
This present study examines the role of technology innovation in testing the environmental Kuznets Curve in Indonesia by taking the annual time series data over the time period of 1980 to 2017. The study used high technology exports as a proxy of technology innovation to examine the long run relationship between economic development, technology innovation and carbon dioxide emission in Indonesia. The author applied the advance econometrics to serve the purpose of investigation and therefore used the FMOLS and DOLS for assessing the presence of long-run relationship between the variables. Utilizing the framework of Kuznets Curve, the results of FMOLS and DOLS approaches confirm the valid long run relationship between technology innovation and environmental degradation in Indonesia. The empirical results indicate that technology innovation has negative and significant impact on carbon dioxide emission long run. Therefore, the findings of the study recommended that technology innovation does not only benefit for the economic development but also helps to reduce the environmental degradation in Indonesia. Keywords: Environmental Kuznets Curve, Technology Innovation, Innovation, Indonesia. JEL Classifications: Q5, Q55, Q56, DOI: https://doi.org/10.32479/ijeep.7230